Simple Determination of Gemifloxacin Levels in Human Plasma using High-Performance Liquid Chromatography-Tandem Mass Spectrometry - Gaeun Kang; Sang Heon Suh; Seong Kwon Ma; Jong-Keun Kim (Journal of Spectroscopy)
Gemifloxacin, a broad-spectrum antibacterial agent of the fluoroquinolone class, is used to treat bacterial infections, including acute bacterial exacerbation of chronic bronchitis and community-acquired pneumonia. This study aimed to develop a simple and robust analysis of gemifloxacin in human plasma by high-performance liquid chromatography-tandem mass spectrometry (LC-MS/MS). The sample was prepared using simple protein precipitation procedures with acetonitrile and separated using the Gemini C18 column with a mobile phase (0.1% formic acid: 0.1% formic acid in acetonitrile = 78: 22 (V/V)). Moxifloxacin was used as an internal standard. The mass spectrometer was operated in the positive ion mode using multiple reaction monitoring. Each precursor ion of gemifloxacin and moxifloxacin was monitored at m/z 390.1/402.1, and their product ions were monitored at m/z 372.3/384.4. The calibration curve showed linearity in 0.005–5 μg/mL with an appropriate correlation coefficient (≥0.99). The variation coefficient of intra- and interprecision values of gemifloxacin was <15%. The intra- and interaccuracy values ranged from 85% to 115%, except for the lower limit of quantification (accuracy range: 80%–120%). The proposed method was performed with a simple preparation step, and moxifloxacin, which is easily accessible, was used as the internal standard. These results suggest that the present assay is a practical analytical method and, therefore, can be readily applied for analysis, including in pharmacokinetic studies and therapeutic drug monitoring of gemifloxacin.